2017
DOI: 10.5032/jae.2017.03293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Annual Community-Focused Agricultural Literacy Event

Abstract: Agricultural literacy programs are effective pathways to informally teach the public about agriculture through stakeholder (attendee and exhibitor) interaction. Such programs are generally evaluated using attendee feedback but fail to include exhibitors' experience. The purpose of this study was to evaluate a local community agricultural event by (a) exploring attendee agricultural literacy, purchasing behavior, and overall experience at the event, and (b) exploring exhibitor experiences at the same event. Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As the global population approaches ten billion people by 2050 the need for agricultural professionals to understand the differences between agricultural literacy and being agriculturally literate is vital to efforts promoting agricultural literacy. Sandlin and Perez (2017) highlighted this need when they found the public had the ability to read (literate) agricultural word and phrases, but did not accurately demonstrate knowledge (literacy) about the relationship between purchasing local products and the impact on the environment. Sandlin and Perez (2017) wrote "[i]n terms of knowledge about locally produced agricultural goods, attendees seemed to overestimate locally grown benefits" (p. 304).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the global population approaches ten billion people by 2050 the need for agricultural professionals to understand the differences between agricultural literacy and being agriculturally literate is vital to efforts promoting agricultural literacy. Sandlin and Perez (2017) highlighted this need when they found the public had the ability to read (literate) agricultural word and phrases, but did not accurately demonstrate knowledge (literacy) about the relationship between purchasing local products and the impact on the environment. Sandlin and Perez (2017) wrote "[i]n terms of knowledge about locally produced agricultural goods, attendees seemed to overestimate locally grown benefits" (p. 304).…”
Section: Introductionmentioning
confidence: 99%
“…Sandlin and Perez (2017) highlighted this need when they found the public had the ability to read (literate) agricultural word and phrases, but did not accurately demonstrate knowledge (literacy) about the relationship between purchasing local products and the impact on the environment. Sandlin and Perez (2017) wrote "[i]n terms of knowledge about locally produced agricultural goods, attendees seemed to overestimate locally grown benefits" (p. 304). Viola, Bianchi, Croce, and Ceretti (2016) found that while consumers tended to read food labels, most struggled with knowledge and understanding.…”
Section: Introductionmentioning
confidence: 99%